Pathogenic bacteria in cheese, raw and pasteurised milk. Issue 6 (14th August 2021) - Bastam, Mahsa Morovati; Jalili, Mahsa; Pakzad, Iraj; Maleki, Abbas; Ghafourian, Sobhan
Abstract: Background: Foodborne diseases, especially those transmitted by milk and its products, are worldwide problem. Milk is not only a complete food but also a unique medium for activating various bacteria such as Listeria monocytogenes, Staphylococcus aureus and Salmonella typhi . In recent years, numerous bacteria with multiple drug resistance patterns have appeared, and there have been many problems in infection control. Today, ranchers use antibiotics for control of the animal disease, and humans are constantly using animal products containing antibiotics. Objective: The purpose of this study was to evaluate the contamination status of raw and pasteurised milk as well as local cheese and to find a rapid Multiplex PCR method for investigation of contamination. Determination of antibiotic resistant isolates is also desirable. Materials and Methods: One hundred samples were collected from livestock and retail outlets using culture and molecular methods to identify S. aureus, L. monocytogenes and S. typhi . The antibiotic resistance pattern was determined for the isolates. Results: In this study, culture results for 100 samples showed 10% S. aureus isolates while no cases of S. typhi and L. monocytogenes were detected. In real‐time qPCR, S. aureus was isolated in 60% ( n  = 60) of samples, S. typhi in 53% ( n  = 53) and L. monocytogenes in 2% ( n  = 2). The results of sensitivity and specificity of Multiplex PCR for the three studied bacteria indicated general specificity of 72% and sensitivity of 80%. Conclusion: Based on the results of this study, it can be concluded that S. typhi, L. monocytogenes and S. aureus are more likely to be detected by real‐time qPCR because of the high sensitivity of this test to culture. Multiplex method was not reliable in this study and cannot be suggested for rapid diagnosis. Abstract : Because of consumption of some milk and dairy product as traditional in Ilam, Iran, we decided to evaluate the microbial contamination in raw milk, cheese and pasteurised milk by culture and molecular methods. Our results showed some of raw milk, cheese and pasteurised milk had microbial contamination. We found the molecular methods are reliable to detect S. aureus, S. typhi and L . monocytogenes . Although, Multiplex PCR is fast, but we could not suggest this method to detect the three studied bacteria.